Analisis Kerjasama Australia-ASEAN dalam Bidang Ekonomi - Vaya Nabila Safitri (Universitas Islam Malang, 2020)
Research conducted to find out what was done by Australia-ASEAN in the economic field. The method used by researchers is deductive, in which the paragraphs are collected in general or the main idea of the paragraphs and then conclusions are drawn specifically. The type of research conducted is qualitative research in which collects data used by researchers, namely Library Studies (Library Research). Based on the results and discussion of ASEAN is an important part of economic prosperity in Australia. As a regional organization in the Southeast Asian region, ASEAN is currently the largest trading partner with Australia. Cooperation between Australia and ASEAN includes the Regional Comprehensive Economic Partnership (RCEP), the ASEAN-Australia Development Cooperation Program (AADCP), the ASEAN-Australia-New Zealand Free Trade Agreement (AANZFTA). Australia has welcomed the cooperation agreement. This cooperation agreement is important for trade in our region which will drive export opportunities for Australian businesses and facilitate more local employment.